Evidence for ProTα-TLR4/MD-2 binding: molecular dynamics and gravimetric assay studies. (July 2015) - Omotuyi, Olaposi; Matsunaga, Hayato; Ueda, Hiroshi
<x xml:space="preserve">Abstract</x> Objective: During preconditioning, lipopolysaccharide (LPS) selectively activates TLR4/MD-2/Toll/IL-1 receptor-domain-containing adaptor inducing IFN-β (TRIF) pathway instead of pro-inflammatory myeloid differentiation protein-88 (MyD88)/MyD88-adaptor-like protein (MAL) pathway. Extracellular prothymosin alpha (ProTα) is also known to selectively activate the TLR4/MD2/TRIF–IRF3 pathway in certain diseased conditions. In the current study, biophysical evidence for ProTα/TLR4/MD-2 complex formation and its interaction dynamics have been studied. Research design and methods: Gravimetric assay was used to investigate ProTα/TLR4/MD-2 complex formation while molecular dynamics (MD) simulation was used to study its interaction dynamics. Results: Through electrostatic interaction, full-length ProTα (F-ProTα) C-terminal peptide (aa 91 – 111) superficially interacts with similar TLR4/MD-2 (KD = 273.36 nm vs 16.07 μg/ml [LPS]) conformation with LPS at an overlapping three-dimensional space while F-ProTα is hinged to the TLR4 scaffold by one-amino acid shift-Mosoian domain (aa-51 – 90). Comparatively, F-ProTα better stabilizes MD-2 metastable states transition and mediates higher TLR4/MD-2 interaction than LPS. Conclusions: ProTα via its C-terminal peptide (aa 91 – 111) exhibits in vitro biophysical contact with TLR4/MD-2 complex conformation recognized by LPS at overlapping LPS-binding positions.